2021
DOI: 10.1002/dvdy.381
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 contributes to phenotypic robustness of the mouse skull

Abstract: Background We compared skull shape and variation among genetically modified mice that exhibit different levels of connexin43 (Cx43) channel function, to determine whether Cx43 contributes to craniofacial phenotypic robustness. Specifically, we used two heterozygous mutant mouse models (G60S/+ and I130T/+) that, when compared to their wildtype counterparts, have an ~80% and ~50% reduction in Cx43 function, respectively. Results Both mutant strains showed significant differences in skull shape compared to wildty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…To determine the tissue‐level developmental processes that link Cx43 function with nasal bone phenotypic variability, we compared development of nasal structures between G60S/+ mutant mice and their WT littermates from postnatal day 0 (P0) to 3 months. Our previous findings demonstrated that the nasal bone phenotype is not present at P0, but that many G60S/+ mice display deviated nasal bones by 3 months 4 . Given the postnatal timing of this aberrant development, and the well‐established role of Cx43 in bone remodeling, 21,22,24 we compared osteoblast and osteoclast numbers at the cortical surfaces of the nasal bones, as well as measures of nasal cortical bone formation using dynamic histology between G60S/+ and WT mice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine the tissue‐level developmental processes that link Cx43 function with nasal bone phenotypic variability, we compared development of nasal structures between G60S/+ mutant mice and their WT littermates from postnatal day 0 (P0) to 3 months. Our previous findings demonstrated that the nasal bone phenotype is not present at P0, but that many G60S/+ mice display deviated nasal bones by 3 months 4 . Given the postnatal timing of this aberrant development, and the well‐established role of Cx43 in bone remodeling, 21,22,24 we compared osteoblast and osteoclast numbers at the cortical surfaces of the nasal bones, as well as measures of nasal cortical bone formation using dynamic histology between G60S/+ and WT mice.…”
Section: Resultsmentioning
confidence: 99%
“…We found that while mean skull shape for both I130T/+ and G60S/+ mutant mice was different from their wild‐type (WT) littermates, increased variation of skull phenotype was observed only in the G60S/+ mice. These results indicated that skull shape variation is robust at 50% Cx43 channel function reduction, but is disrupted when channel function is reduced to 20%, demonstrating a threshold effect of Cx43 function on phenotypic variability of the skull 4 . The greatest shape variation in the G60S/+ mice was localized to the bones of the face, and this variation became more marked by 3 months of age compared to neonate mice.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations